Hierarchical Classification of Narwhal Subpopulations Using Social Distance. Issue 2 (10th December 2019) - Charry, Bertrand; Marcoux, Marianne; Cardille, Jeffrey A.; Giroux‐Bougard, Xavier; Humphries, Murray M.
Abstract : This paper provides a novel assessment of narwhal summer stock definition based on swimming distance and a first look at sex distribution and narwhal newborns at a large scale across the Canadian Arctic Archipelago. This highlights the potential of a long‐term aerial digital database to provide critical information to future decision makers and northern people for narwhal management and conservation in the eastern Canadian archipelago. ABSTRACT: Effective wildlife management and conservation require knowledge of distribution, sex composition, and age structure of a population. We explored the distribution of the Baffin Bay narwhal ( Monodon monoceros ) population in August 2013 by documenting sex and age distribution across the Canadian Arctic Archipelago covering 2, 317, 152 km 2 . For 6, 314 narwhals identified in 3, 393 aerial images taken across the Eastern Canadian Arctic, we calculated a matrix of swimming distances between all individuals. We then used a quantitative clustering approach to partition our dataset (partitioning around the medoids). The clusters obtained from the analysis supported the delimitation of the 5 narwhal management stocks currently used by the Department of Fisheries and Oceans but did not support the hypothesized division of Jones Sound and Smith Sound stocks. Across the 5 clusters, male:female ratios varied between 0.72 and 1.44 and the proportion of newborns relative to the number of females varied between 0.07 and 0.18. As a highly detailed snapshot of narwhal distribution across a very large region, our study is a step toward better documentation of the basic population information required for stock assessment, sustainable harvest, and habitat protection of narwhals in an era of rapid Arctic change. © 2019 The Wildlife Society.